Variabilidade da precipitação pluviométrica na bacia hidrográfica dos rios Vacacaí e Vacacaí-Mirim - Bammesberger, Andressa (2020)
The general objective of the present study was to analyze the influence of altitude on the distribution and the trend of seasonal regimes of historical series of pluviometric precipitation in the Hydrographic Basin of the Rivers Vacacaí and Vacacaí-Mirim, in Rio Grande do Sul. An average homogeneity of maximum and minimum, was analyzed using the cluster method, and an analysis of rainfall estimation, maximum and minimum media, as a function of altitude using the principal component analysis (PCA) method. Afterwards, choose to use three pluviometric stations inserted in the hydrographic basin in question, represented by different altitudes, station e6 (Range 2, 200 m), e8 (Range 1, 120 m) and e9 (Range 3, 420 m). The rainfall (summer, December, January and February), autumn (March, April and May), winter (June, July and August) and spring (September, October and November) were evaluated. Use the Kruskal-Wallis statistical method and linear regression to analyze the trend in the distribution of rainfall. He concluded that the altitude between the bands was heterogeneous, however, the tendency to capture in each band shown is homogeneous, with little variation in the volume of precipitation in the pluviometric stations. In addition, there is a tendency to increase rainfall in the summer, winter and spring seasons in the e6, e8 and e9 rain seasons over the years. The fall showed a reduction in rainfall over the years. The El Niño phenomenon plays a major role in extreme events in the three studied rainfall stations. And also, even with different altitudes, similar to the similarity of the pluviometric volume in the seasons (summer, autumn, winter and spring) in several years, and in several extreme events.